Alejandro M. Rabinovich. Anatomía del pánico. La batalla de Huaqui, o la derrota de la revolución (1811). Buenos Aires: Sudamericana, 2017, 283 páginas (Quinto Sol, 2018)
Reseña de Alejandro M. Rabinovich. Anatomía del pánico. La batalla de Huaqui, o la derrota de la revolución (1811). Buenos Aires: Sudamericana, 2017, 283 páginas.